2014
DOI: 10.7314/apjcp.2014.15.9.3911
|View full text |Cite
|
Sign up to set email alerts
|

Application of Tumor Markers SCC-Ag, CEA, and TPA in Patients with Cervical Precancerous Lesions

Abstract: Background: To determine the potential clinical utility of tumor markers CEA, TPA, and SCC-Ag for early detection of cervical precancerous lesions. Materials and Methods: A case-control study was carried out on 120 women (46 patients with histologically confirmed cervical precancerous lesions and 74 healthy controls). The significance of serum selected tumor markers in early detection of cervical intraepithelial neoplasia (CIN) were assessed. Results: Of the case group, the rates of CIN I, II, III, was 69.6%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Adopting individual cutoff points based on the ROC curve is important because it can increase sensitivity. This approach, in turn, may increase the chance of detecting precancerous states and enable earlier detection of recurrence [ 13 – 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adopting individual cutoff points based on the ROC curve is important because it can increase sensitivity. This approach, in turn, may increase the chance of detecting precancerous states and enable earlier detection of recurrence [ 13 – 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is the third most common gynecologic cancer and the fourth leading cause of cancer death among women worldwide [ 1 ]. It has been demonstrated that persistent infection with high risk human papilloma virus (HR HPV) types playsa major role in the development of cervical intraepithelial neoplasia and cervical cancer [ 2 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the same tumors can express several different unique antigens [ 13 , 14 ]. Recently, normal cervical cells have been reported to synthesize and secrete the tumor marker carcinoembryonic antigen (CEA) as a frequent constituent of normal cervical mucus [ 15 ]. The cancer antigen 125 (CA125), a transmembranes glycoprotein, is a tumor marker mainly utilized for the diagnosis and treatment of epithelial ovarian cancer and cervical cancer [ 16 ].…”
Section: Introductionmentioning
confidence: 99%